Om as familie in Suid-Afrika te leef: Interkulturele Bybelstudie as transformatiewe krag in die samelewing - Jonker, Louis (Nederduitse Gereformeerde Teologiese Tydskrif, 2014)
Living as a family in South Africa: Intercultural Bible study as a transformational power in society This contribution describes a research project in empirical hermeneutics which departed from the hypothesis that a development of hermeneutical skills among Christian communities for reading the Bible together with “the Other” could contribute significantly towards the fostering of interculturality in the broader South African society. Additionally, it was hypothesized that the studying of the dynamics of intercultural Bible reading could provide us with better insight into the dynamics of a shift from multiculturality to interculturality. The present article reports on the results achieved in the investigation. It has been established that fear for and a lack of knowledge of “the Other” are important reasons for the lack of interculturality in society. It has also been confirmed that the Bible – as liminal “meeting place” for people from different cultures – can foster a sense of family and hospitality in the South African nation.